PENGABDIAN MASYARAKAT : PEMERIKSAAN IVA TEST PADA WANITA USIA SUBUR DI KELURAHAN JATISARI KECAMATAN MIJEN - Novita Nining Anggraini; Fitriani Nur Damayanti; Lia Mulyanti (Universitas Muhammadiyah Semarang, 2017)
Test The purpose of community service is to improve the knowledge of women of childbearing age in the examination of IVA Test, early detection of cervical cancer in women of childbearing age. The method used to achieve these goals is by participatory action research among others through Forum Group Discusion (FGD). Outcomes in these activities in the form of goods and services. Outcomes in the form of goods as the draft articles of scientific publications through proceedings. The outcomes in the form of services is health education of IVA Test and examination of IVA Test in women of childbearing age.Keywords: IVA Test, Women of childbearing age